Brazilian Artisanal Cheeses: Diversity, Microbiological Safety, and Challenges for the Sector - Pineda, Ana Paulina Arellano; Campos, Gabriela Zampieri; Pimentel-Filho, Natan Jesus; Franco, Bernadette Dora Gombossy de Melo; Pinto, Uelinton Manoel (Frontiers in Microbiology, 2021)
Artisanal cheeses made with raw milk are highly appreciated products in Brazil. Most of these cheeses are produced in small facilities across different production regions in the country, some of which have been granted a protected designation of origin and are award winners. The most prominent state that manufactures these products is Minas Gerais, but production is also gaining strength in other Brazilian states. The major challenge faced by artisanal cheese production is related to microbial risks associated with foodborne pathogens when the quality of the raw milk is unsatisfactory. Regulations created for the dairy industry are constantly been revised and adapted, considering the small-scale production of Brazilian artisanal cheeses, in order to guarantee safety at all steps of cheese production and commercialization. This text presents a summary of the huge diversity of artisanal cheeses produced in the country, grouped by geographical regions, and reviews the current challenges faced by producers and government considering the safety of these cheeses.